Management of periodontal hard tissue related complications in orthodontic treatment - BAO Jiaqi, WANG Zhongxiu, FENG Yimiao, LEI Lihong, CHEN Lili (Kouqiang yixue)
As orthodontic treatment improves malocclusion and enhances oral health quality, the number of orthodontic patients is steadily increasing. However, a lack of understanding of periodontal inflammation and the health of periodontal supporting tissues during orthodontic treatment can lead to alveolar bone destruction and resorption. This, in turn, results in periodontal hard tissue-related complications such as bone fenestration, bone dehiscence, abnormal interradicular distance, and tooth mobility or loss. Currently, these complications present a significant challenge in orthodontic practice. This paper provides a comprehensive overview of common periodontal hard tissue-related complications during orthodontic treatment, along with clinical prevention and management strategies. A typical case of multidisciplinary periodontal treatment is also presented, addressing alveolar bone resorption and tooth mobility in the upper anterior teeth caused by improper orthodontic treatment. This report aims to offer valuable reference for clinicians.